Genome-wide analysis of m6A-modified circRNAs in the mouse model of myocardial injury induced by obstructive sleep apnea - Jiuhuang Lan; Yuhui Wang; Chang Liu; Hongli Chen; Qingshi Chen (BMC Pulmonary Medicine)
Abstract Background The peculiar expression of N6-methyladenosine (m6A) in Circular RNAs (circRNAs) is closely linked to the occurrence of many diseases. However, roles of m6A-modified circRNAs in OSA-induced cardiovascular disease are unknown. Here, we use bioinformatics analysis to investigate the expression profiles of m6A-modified circRNAs and reveal their potential functional roles in the mouse models of chronic intermittent hypoxia (CIH). Methods Firstly, the expression profiles of m6A-modified circRNA in left ventricular tissue of the CIH mouse model were examined using circRNA microarray analysis. Then, the expression level of selected circrRNA was compared by folding change filtration, and the consistency between them and microarray results was verified by MeRIP-qPCR. GO analyses and KEGG analyses were conducted to predict the potential functions of these m6A-modified circRNAs. Finally, we conducted a ceRNA analysis, and a network was constructed to clarify the relationship between the selected circRNAs and miRNAs as well as the targeted genes. Results In total, 255 circRNAs with m6A peaks in CIH-treated cardiac tissues were identified. 250 were up-regulated, 5 were down-regulated. The results of MeRIP-qPCR were consistent with the microarray results. 73 pathways were detected in the up-regulated transcripts and no relevant pathways were detected in the down-regulated transcripts. Finally, three circRNAs (mmu_circRNAs_22543, mmu_circRNAs_29768, and mmu_circRNAs_34841) were selected for ceRNA analysis, and the circRNA-miRNA-mRNA network was constructed. Conclusion Our findings are the first to show that m6A-modified circRNAs play a key role in OSA-induced cardiovascular disease. This study highlights the pivotal role of m6A-modified circRNAs in regulating gene expression and their potential implications in understanding the molecular pathogenesis of OSA-induced cardiac injury.